WTO negotiations on environmental goods and services : a potential contribution to the Millennium Development Goals - Cottier, Thomas (UN New YorkUS, 2009)
Assesses recent developments in negotiations and offers a critical analysis. Seeks to develop alternative avenues and methods for the conduct of future negotiations in the field. Suggests establishing strong linkages between the UN Millennium Development Goals and environmental goods and services negotiations.